Seasonal and spatial variability of pelagic fishes in relation to environmental variability in St Helena Bay - Mushanganyisi, Kanakana S (Department of Biological Sciences, 2020)
The St Helena Bay Monitoring Line (SHBML) stretches 197 nautical miles off Elands Bay on the west coast of South Africa. It is an extensive long term project on environmental monitoring, running from 2000 till 2012 on an almost monthly basis but currently running on a quarterly basis. It extends through the nursery grounds and part of the transport zone for hydrology and productivity in areas that are significant to early life history of small pelagic fish. Environmental, acoustic and zooplankton data have been collected along the SHBML to obtain information on ocean environment, pelagic fish abundance and also zooplankton abundance. This study used an interdisciplinary approach, analysing historical data collected during biannual surveys of small pelagic fish, to investigate seasonal and spatial variability of pelagic fishes in relation to environmental variability in St Helena Bay. Surface values from 2000 to 2010 of temperature, salinity, oxygen and chlorophyll were analysed in relation to zooplankton and fish densities. The results show partial / weak seasonality of SST in offshore and also in coastal stations. Zooplankton, chlorophyll and oxygen show limited seasonality only in nearshore stations. Strong cross-shelf patterns of SST, chlorophyll, salinity, oxygen, zooplankton biomass and fish abundance were noted. These were expected results from a coastal upwelling system where primary productivity during summer is increased in the nearshore zone. There was a positive relationship between salinity and SST (r = 0.821, p< 0.0001) and a negative relationship between chlorophyll and SST (r = -0.549, p< 0.001), as would be expected in a coastal upwelling environment. When other variables were examined (also in pairs), there were no relationships between SST and oxygen, fish and zooplankton, fish and chlorophyll, fish and SST, fish and oxygen, and chlorophyll and zooplankton. A GLM was fitted to the data to investigate the relationship of pelagic fish density with zooplankton biovolume, chlorophyll, SST and oxygen; the GLM results showed a negative relationship between zooplankton abundance and pelagic fish (t=-1.980, p=0.049). Based on these results, it appears that the SHBML data were not able to pick up seasonal signals but have shown interannual variability and also some inshore-offshore differences.